Voices of Islamic Reform: A Study on Islamic Press in Indonesia, 1900-1942 - Emalia, Imas (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Since the end of the 19th century, indigenous-run press had developed rapidly in various regions of the East Indies (Indonesia now), especially in Java and Sumatra. In the beginning of the 20th century, the development of indigenous-run press developed more rapidly than before, in consequence of the fact that the press became the means of struggle used by numerous social, political, and religious organizations. The development of religious organizations, especially in Java and Sumatra, were influential as the press was used as a means for preaching on religious matters and was further expanded on social, economic, and political matters. It was stated that Islamic press played a significant role in the lives of the people. This development can be observed by the emergence of Islamic magazines pioneered by âAl-Moenirâ (Enlightenment), in 1911-1916, which was circulated in West Sumatra. This magazine was influenced by the publication of âAl-Imamâ (Leader), in 1906-1909, which was circulated in Singapore. While in Java, Islamic organizations such as SI (Sarekat Islam or Islamic League), Muhammadiyah (Followers of Prophet Muhammad), and PO (Persjarikatan Oelama or Islamic Scholars League) also actively made use of newspapers and magazines as their means of struggle. Through news and views, Islamic press called upon people to keep up with progress. Through Islamic press, people also were called upon to learn science, religion, and were given the awareness of nationalism. KEY WORDS: Islamic society, indigenous Islamic press, colonial Islamic politics, Islamic progress, and Netherlands Indies government.About the Author: Imas Emalia, M.Hum. is a Lecturer at the Department of History and Islamic Civilization, Faculty of Adab and Humanities UIN (Universitas Islam Negeri or State Islamic University) Syarif Hidayatullah in Jakarta, Indonesia. For academic interests, the author is able to be contacted via mobile phone at: +628176753947 or via e-mail at: imas.emalia@gmail.comHow to cite this article? Emalia, Imas. (2016). âVoices of Islamic Reform: A Study on Islamic Press in Indonesia, 1900-1942â in TAWARIKH: International Journal for Historical Studies, Vol.7(2) April, pp.201-224. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (January 4, 2016); Revised (March 2, 2016); and Published (April 28, 2016).